PELATIHAN PENGAMAN INSTALASI LISTRIK SESUAI PERSYARATAN UMUM INSTALASI LISTRIK 2011 SERTA AMANDEMEN 2014 - Swamardika, I.B.A.; Amrita, A.A.N.; Arjana, I.G.D.; Partha, C.G.I. (Buletin Udayana Mengabdi, 2018)
Electricity is a very vital need for the life of the community it is today. Electricity became the primary needs of the relatively inexpensive price because in addition is also very helpful in everyday life. In addition to electricity has huge advantages, electricity also has a hazard that can lead to accidents such as fire, electrical current was stung and damage electrical equipment. Electrical hazards can be eliminated by following all electrical installation requirements. Danger of electric shock and fires can be corrected with electrical installation safety contained in the 2011 electrical installation General requirements (Amendment 2011serta year 2014 PUIL, who hinted to secure the environment in this securing human safety, mandatory use of electrical installation in accordance with the National Standard safety Indonesia (SNI). In this devotion, it will be given an explanation and electric installation training in accordance with the General requirements of the electrical installation for the community in the village of Sinduwati, district Sidemen Karangasem Regency.